Aluminum-doped zinc oxide transparent conductive hydrophobic thin film and preparation method thereof
Patent Information
- Application Number
- CN202611133786.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-23
AI Technical Summary
[0009]现有技术中对导电性能和疏水性能的研究常采用不同的调控方式,难以在同一过程中同时实现良好的导电性和疏水性
(1)本发明提供的铝掺杂氧化锌透明导电疏水薄膜兼具接触角为105-125°和电阻率为1×10-3-1.5 Ω·cm的综合性能。
Smart Images

Figure CN122968037A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of transparent conductive oxide thin film technology, specifically relating to an aluminum-doped zinc oxide transparent conductive hydrophobic thin film and its preparation method. Background Technology
[0002] Transparent conductive oxide (TCO) thin films are key functional materials in optoelectronic devices and are widely used in thin-film solar cells, flat panel displays, touch screens, and energy-saving building glass. With indium tin oxide (ITO) limited by the scarcity and high cost of indium resources, aluminum-doped zinc oxide (AZO) has become the most promising alternative material due to its abundant raw materials, non-toxicity, stability, and excellent photoelectric properties.
[0003] With the development of building-integrated photovoltaics, automotive displays, and outdoor optoelectronic devices, the demand for multifunctional integrated transparent conductive cover materials with anti-fouling, scratch-resistant, and long-life properties is becoming increasingly urgent. Hydrophobic surfaces, which allow water droplets to roll in a spherical manner, help reduce the adhesion of dust and polar liquid contaminants to the film surface, thus becoming an important research direction in surface anti-fouling technology. However, current research on AZO thin films has long focused on the modulation of photoelectric properties, with insufficient attention paid to the simultaneous improvement of their surface wettability and mechanical properties.
[0004] Patent document CN112593194A discloses a method for preparing a large-area aluminum-doped zinc oxide transparent conductive film with high light transmittance and high electrical conductivity. The method employs radio frequency magnetron sputtering with a hydrogen and argon mixture as the working gas to deposit the AZO film at a relatively low working pressure (0.2 Pa to 2 Pa). This method effectively improves the conductivity of the AZO film by introducing hydrogen, but it does not address the control of the film surface wettability.
[0005] Patent document CN119800311A discloses a method for preparing a UV-shielding hydrophobic transparent thin film. It employs radio frequency magnetron sputtering to deposit a single-layer ZnO thin film using pure ZnO as the target material, achieving both UV shielding and hydrophobic properties. However, this thin film is a pure ZnO system without aluminum doping modification and therefore lacks the conductivity required for a transparent conductive thin film.
[0006] On the other hand, while existing organic low surface energy coatings (such as fluorosilane modification) can achieve high contact angles, they have low film density and insufficient hardness (usually not higher than 2H), resulting in serious deficiencies in weather resistance and wear resistance. Meanwhile, micro-nano structured ZnO hydrophobic films prepared by sol-gel or hydrothermal methods have loose film layers, weak adhesion to the substrate, and generally lower hardness than 3H. Furthermore, they have long processing cycles and poor uniformity, making them unsuitable for large-scale industrial continuous production.
[0007] In ZnO and ZnO-doped systems, ZnO, as a polar metal oxide with a wurtzite structure, has uncoordinated atoms and defect structures on its surface. These surface states collectively influence the adsorption behavior of water molecules. Oxygen vacancies, as a defect structure in the ZnO system, also affect the carrier concentration, thus impacting conductivity. Therefore, in the traditional preparation of aluminum-doped zinc oxide thin films, a high concentration of oxygen vacancies is usually introduced to achieve high conductivity, a process that often involves an increase in hydrophilicity.
[0008] However, the effect of oxygen vacancies on wettability is not unidirectional. On the one hand, oxygen vacancies, as active sites on the surface, readily adsorb water molecules, making the surface more hydrophilic. On the other hand, these active sites can also capture organic molecules in the air. Organic molecules occupy the surface through these active sites and form a dense adsorption layer. This adsorption layer can shield the high surface energy of the substrate, causing the wettability of the film surface to become hydrophobic.
[0009] Current technologies often employ different control methods to study conductivity and hydrophobicity, making it difficult to simultaneously achieve good conductivity and hydrophobicity in the same process. Therefore, it is of great significance to prepare AZO thin films that combine conductivity and hydrophobicity by controlling the surface state of the film while ensuring conductivity. Summary of the Invention
[0010] The purpose of this invention is to provide an aluminum-doped zinc oxide transparent conductive hydrophobic thin film and its preparation method. By controlling the sputtering power density and working pressure during the DC magnetron sputtering process, the thin film can obtain good hydrophobic properties while having good conductivity.
[0011] In a first aspect, the present invention discloses an aluminum-doped zinc oxide transparent conductive hydrophobic film, comprising a transparent substrate and an aluminum-doped zinc oxide film layer deposited on the surface of the transparent substrate, wherein the mass ratio of aluminum oxide to zinc oxide in the aluminum-doped zinc oxide transparent conductive hydrophobic film is 0.02~0.04:1. The resistivity of the aluminum-doped zinc oxide transparent conductive hydrophobic film is 1×10⁻⁶. -3 ~1.5 Ω·cm; The surface static water contact angle of the aluminum-doped zinc oxide transparent conductive hydrophobic film is 105~125°.
[0012] The transparent substrate is transparent glass.
[0013] Preferably, the aluminum-doped oxide transparent conductive hydrophobic film has an average transmittance of 84-89% (including the substrate) in the visible light band of 400-800 nm.
[0014] Preferably, the aluminum-doped zinc oxide thin film layer has a (002) crystal plane orientation. The (002) crystal plane orientation is beneficial for electron migration and maintains the good conductivity of the thin film.
[0015] Preferably, the pencil hardness of the aluminum-doped zinc oxide transparent conductive hydrophobic film is not less than 9H.
[0016] Preferably, the surface of the aluminum-doped zinc oxide thin film layer has a nanoscale surface texture of island-like protrusions, interwoven nanoridges, or interconnected networks. This texture is formed under high operating pressure (3-4 Pa) by a shortened mean free path and reduced kinetic energy of sputtered particles, which promotes the full diffusion and localized nucleation of deposited atoms on the substrate surface. Under the Wenzel wetting model, this micro / nano rough structure can effectively amplify the apparent contact angle of the intrinsically hydrophobic surface, thereby achieving a macroscopic hydrophobic effect by increasing the contact angle from the intrinsic value (approximately 90-100°) to 105-125°.
[0017] Preferably, the root mean square roughness of the aluminum-doped zinc oxide thin film layer is 2~14 nm. This roughness range provides sufficient physical unevenness to enhance the hydrophobic gain brought about by the Wenzel effect, while avoiding optical scattering loss caused by excessive roughness, thereby ensuring that the average transmittance in the visible light band is maintained above 82%, achieving a balance between hydrophobicity and light transmittance.
[0018] On the other hand, this invention discloses a method for preparing an aluminum-doped zinc oxide transparent conductive hydrophobic thin film, comprising depositing an aluminum-doped zinc oxide thin film layer on a transparent substrate in a single step using a DC magnetron sputtering method, with specific process parameters as follows: (1) Target material: Aluminum-doped zinc oxide ceramic target material with an alumina to zinc oxide mass ratio of 0.02:1; (2) Sputtering working gas: Argon gas with a purity of not less than 99.99%, wherein the sputtering working gas is composed of argon gas; (3) Sputtering power density: 0.5~2 W / cm 2 ; (4) Sputtering working pressure: 3~4 Pa; (5) Substrate temperature: 20~400 ℃.
[0019] In the range of 0.5~2 W / cm 2 The low sputtering power density and the high working pressure of 3~4 Pa work together to ensure that the sputtered particles have a suitable energy state when they reach the substrate, which affects the formation of the thin film and makes the final thin film have both good conductivity and hydrophobicity.
[0020] Substitutional doping of aluminum atoms in the bulk phase can provide the main charge carriers and maintain a moderate oxygen vacancy concentration to help regulate resistivity, enabling the thin film to achieve 1×10⁻⁶.-3 The resistivity is ~1.5 Ω·cm. Simultaneously, the low sputtering power density effectively suppresses high-energy particle bombardment and excessively fast Al2O3 sputtering. 3+ The substitution-induced generation of excess oxygen vacancies allows for the retention of appropriately concentrated coordinating unsaturated active sites on the surface and at grain boundaries. This avoids excessive enrichment of active sites that could exacerbate hydrophilicity, while also providing sufficient adsorption sites for subsequent adsorption of organic molecules from the air and the in-situ formation of a dense hydrophobic coating.
[0021] When the deposited film is exposed to the atmosphere, the coordinating unsaturated active sites on the surface preferentially capture water molecules and trace organic molecules from the air through enhanced electrostatic and induced interactions. These captured species gradually assemble into a dense nanoscale organic adsorption layer. This adsorption layer effectively shields the high surface energy sites of the substrate and reduces the solid-liquid interfacial tension, thus giving the film surface significant hydrophobic properties. Furthermore, this adsorption is regulated by surface defect chemistry, and the density and stability of the adsorption layer are superior to those of conventional oxide surfaces without specific defects.
[0022] Furthermore, high operating pressure shortens the mean free path of sputtered particles, reduces their kinetic energy upon reaching the substrate, and promotes localized nucleation and diffusion growth of deposited atoms on the substrate surface, spontaneously forming island-like, interwoven nanoridges, or interconnected network-like nanoscale surface textures. These nanotextures can further amplify the apparent contact angle through the Wenzel wetting effect, synergistically achieving a hydrophobic effect of 105-125° with the surface adsorption layer.
[0023] The AZO thin film prepared under these process conditions exhibits high bulk density and good crystallinity, with a pencil hardness of no less than 9H. Simultaneously, the surface adsorption layer is at the molecular level, which does not compromise the mechanical and optical properties of the film, successfully achieving a synergistic effect of optical transmittance, electrical conductivity, surface hydrophobicity, and high mechanical strength.
[0024] Preferably, the sputtering power density is 1-2 W / cm². 2 Within this power range, sputtered particles possess moderate kinetic energy and deposition rate, ensuring both dense film growth and good crystallization with preferred orientation of the (002) crystal plane, while effectively suppressing high-energy particle bombardment and excessively rapid Al deposition at excessively high power densities. 3+ The substitution-induced generation of excess oxygen vacancies avoids the over-enrichment of surface active sites, which would exacerbate hydrophilicity. At the same time, the film surface retains a suitable concentration of surface active sites, which can preferentially capture organic molecules in the air through enhanced electrostatic and inductive interactions, promoting the subsequent self-assembly on the surface to form a dense low surface energy adsorption layer, thus endowing the film with hydrophobic properties.
[0025] Preferably, the temperature of the transparent substrate is 20-400 ℃.
[0026] More preferably, the temperature of the transparent substrate is 300-400 °C. This high temperature range is beneficial for enhancing the migration and diffusion ability of sputtered atoms on the substrate surface, promoting grain growth and (002) preferred orientation development, reducing grain boundary scattering, and increasing carrier mobility, thereby obtaining a lower resistivity. At the same time, the suitable high temperature is conducive to the formation of point defects such as oxygen vacancies with appropriate concentrations inside the film. These defects can enhance the surface affinity for organic molecules in the air, promote the formation of a dense organic adsorption layer, and thus improve the water contact angle of the film.
[0027] The present invention also provides the application of the aluminum-doped zinc oxide transparent conductive hydrophobic film in solar cells, flat panel display panels, touch screens, optical lenses, transparent electric heating devices, anti-fouling coatings for architectural glass or automotive glass.
[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The aluminum-doped zinc oxide transparent conductive hydrophobic thin film provided by the present invention has both a contact angle of 105-125° and a resistivity of 1×10⁻⁶. -3 Overall performance of -1.5 Ω·cm.
[0029] (2) This invention employs a synergistic process of low sputtering power density and high operating pressure, requiring no post-modification with low surface energy materials, and can achieve thin films that maintain usable conductivity (resistivity 1×10⁻⁶). -3 While achieving a surface energy of -1.5 Ω·cm, highly active surface sites are enriched on the film surface and at grain boundaries, enabling the film to spontaneously form a low surface energy adsorption layer after exposure to air, thus providing a basis for the hydrophobic properties of the film surface.
[0030] (3) High working pressure can induce the formation of controllable nanoscale surface texture, and without significantly losing light transmittance, the hydrophobic properties of the film can be amplified in synergy with the Wenzel effect and surface chemical state. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the layer structure of the aluminum-doped zinc oxide transparent conductive hydrophobic thin film described in this invention; Figure 2 The transmittance spectrum of the thin film prepared in Example 1 in the wavelength range of 300 nm-1100 nm (including glass substrate). Figure 3 The static water contact angle test diagram of the thin film surface prepared in Example 1; Figure 4 X-ray diffraction (XRD) pattern of the thin film prepared in Example 1; Figure 5 The surface morphology of the thin film prepared in Example 1 is shown in the scanning electron microscope (SEM) image. Figure 6 Atomic force microscopy (AFM) morphology image of the thin film prepared in Example 1; Figure 7 The graph shows the pencil hardness test results of the thin film prepared in Example 1; Figure 8 The fine O1s spectrum of the thin film prepared in Example 2 is shown. Figure 9 The graph shows the variation of static water contact angle on the surface of thin films prepared under different process conditions, where (a) represents different working pressures and (b) represents different substrate temperatures. Figure 10 The static water contact angle test diagram of the thin film surface prepared in Comparative Example 1; Figure 11 The static water contact angle test diagram of the thin film surface prepared for Comparative Example 2 is shown. Detailed Implementation
[0032] The present invention will be further illustrated below through specific embodiments. Unless otherwise specified, the materials, reagents, equipment, and methods used in the following embodiments are all conventional materials, reagents, equipment, and methods in the art, and will not be described in detail here. In all the following embodiments, the thin film resistivity is tested using the four-probe method at room temperature, the surface static water contact angle is tested using the seated drop method with deionized water as the test droplet at room temperature, and the pencil hardness is tested according to the GB / T 6739-2022 standard.
[0033] The structures of the aluminum-doped zinc oxide transparent conductive hydrophobic films obtained in the following embodiments are as follows: Figure 1 As shown, it consists of a substrate 1 and an aluminum-doped zinc oxide thin film layer 2 deposited on the substrate. Specifically, an ultra-white glass with a thickness of 1.8 mm is used as the substrate. The substrate is ultrasonically cleaned with anhydrous ethanol and deionized water for 5 min each, and then dried with nitrogen gas before use.
[0034] Example 1 In this embodiment, an AZO target with an alumina to zinc oxide mass ratio of 0.02:1 was selected. The sputtering process conditions were: substrate temperature of 400℃ and AZO target sputtering power density of 2 W / cm³. 2 The working atmosphere in the magnetron sputtering cavity is Ar, the gas flow rate is 30 sccm, the working pressure is 4 Pa, and the deposition time is adjusted according to the target thickness. The film thickness in this embodiment is approximately 275 nm.
[0035] The aluminum-doped zinc oxide transparent conductive hydrophobic thin film prepared in this embodiment has the following properties: (1) Optical performance: The peak transmittance in the wavelength range of 300 nm-1100 nm is 90.9% (corresponding to a wavelength of 634 nm, including the glass substrate), and the average transmittance in the wavelength range of 400 nm-800 nm is 86.0% (including the glass substrate). See [reference needed]. Figure 2 ; (2) Electrical properties: The thin film resistivity is 1.0 × 10⁻⁶. -3 Ω·cm; (3) Hydrophobic properties: The static water contact angle of the surface is 125° (see Figure 3 ); (4) Surface morphology: such as Figure 4 As shown, the preferred orientation of the thin film crystal is the (002) crystal plane; as Figure 5 The scanning electron microscope image shown reveals that the film surface exhibits an island-like grain cluster morphology, with the grains separated by shallow nanoscale trenches. No pore structures penetrating the film thickness were observed. Figure 6 The atomic force microscopy image shown indicates that the root mean square roughness of the surface measured in a 2 μm × 2 μm scanning range is 10.5 nm. (5) Mechanical properties: A 9H pencil did not leave any visible scratches on the film surface, and the pencil hardness was not lower than 9H (see Figure 7 ).
[0036] Example 2 In this embodiment, an AZO target with an alumina to zinc oxide mass ratio of 0.02:1 was selected. The sputtering process conditions were: substrate temperature of 400℃ and AZO target sputtering power density of 2 W / cm³. 2 The working atmosphere in the magnetron sputtering cavity is Ar, the gas flow rate is 30 sccm, the working pressure is 3 Pa, and the deposition time is adjusted according to the target thickness. The film thickness in this embodiment is approximately 170 nm.
[0037] The aluminum-doped zinc oxide transparent conductive hydrophobic thin film prepared in this embodiment has the following properties: (1) Optical performance: The peak transmittance in the wavelength range of 300 nm to 1100 nm is 92.5% (corresponding wavelength of 583 nm, including glass substrate), and the average transmittance in the wavelength range of 400 nm to 800 nm is 88.1% (including glass substrate). (2) Electrical properties: The thin film resistivity is 1.36 × 10⁻⁶. -3 Ω·cm; (3) Hydrophobic properties: The static water contact angle of the surface is 122°; (4) Surface morphology: The root mean square roughness of the surface is 4.36 nm; (5) Mechanical properties: A 9H pencil does not leave visible scratches on the film surface, and the pencil hardness is not less than 9H.
[0038] The thin film prepared in this embodiment was analyzed by X-ray photoelectron spectroscopy (XPS), and its O1s fine spectrum is as follows: Figure 8 As shown in the figure, the surface hydroxyl peak at 531.6 eV is dominant (82.79%), while the adsorbed oxygen / free hydroxyl peak at 532.8 eV is a minor component (17.21%). This result indicates that the film surface is coated with a dense capping layer mainly composed of oxygen-containing organic groups. This capping layer effectively shields the high surface energy sites of the substrate, endowing the film with hydrophobic properties.
[0039] Example 3 In this embodiment, an AZO target with an alumina to zinc oxide mass ratio of 0.02:1 was selected. The sputtering process conditions were: substrate temperature of 25°C and AZO target sputtering power density of 2 W / cm³. 2 The working atmosphere in the magnetron sputtering cavity is Ar, the gas flow rate is 30 sccm, the working pressure is 3 Pa, and the deposition time is adjusted according to the target thickness. The film thickness in this embodiment is approximately 150 nm.
[0040] The aluminum-doped zinc oxide transparent conductive hydrophobic thin film prepared in this embodiment has the following properties: (1) Optical performance: The peak transmittance in the wavelength range of 300 nm to 1100 nm is 91.0% (corresponding to a wavelength of 634 nm, including the glass substrate), and the average transmittance in the wavelength range of 400 nm to 800 nm is 85.4% (including the glass substrate). (2) Electrical properties: The thin film resistivity is 1.48 Ω·cm; (3) Hydrophobic properties: The static water contact angle of the surface is 110°; (4) Surface morphology: The root mean square roughness of the surface is 7.1 nm; (5) Mechanical properties: A 9H pencil does not leave visible scratches on the film surface, and the pencil hardness is not less than 9H.
[0041] Example 4 In this embodiment, an AZO target with an alumina to zinc oxide mass ratio of 0.02:1 was selected. The sputtering process conditions were: substrate temperature of 300℃ and AZO target sputtering power density of 2 W / cm³. 2 The working atmosphere in the magnetron sputtering cavity is Ar, the gas flow rate is 30 sccm, the working pressure is 3 Pa, and the deposition time is adjusted according to the target thickness. The film thickness in this embodiment is approximately 170 nm.
[0042] The aluminum-doped zinc oxide transparent conductive hydrophobic thin film prepared in this embodiment has the following properties: (1) Optical performance: The peak transmittance in the wavelength range of 300 nm to 1100 nm is 91.7% (corresponding to a wavelength of 625 nm, including the glass substrate), and the average transmittance in the wavelength range of 400 nm to 800 nm is 85.9% (including the glass substrate). (2) Electrical properties: The thin film resistivity is 4.12 × 10⁻⁶. -3 Ω·cm; (3) Hydrophobic properties: The static water contact angle of the surface is 116°; (4) Surface morphology: The root mean square roughness of the surface is 10.9 nm; (5) Mechanical properties: A 9H pencil does not leave visible scratches on the film surface, and the pencil hardness is not less than 9H.
[0043] Example 5 In this embodiment, an AZO target with an alumina to zinc oxide mass ratio of 0.02:1 was selected. The sputtering process conditions were: substrate temperature of 100℃ and AZO target sputtering power density of 2 W / cm³. 2 The working atmosphere in the magnetron sputtering cavity is Ar, the gas flow rate is 30 sccm, the working pressure is 3 Pa, and the deposition time is adjusted according to the target thickness. The film thickness in this embodiment is approximately 160 nm.
[0044] The aluminum-doped zinc oxide transparent conductive hydrophobic thin film prepared in this embodiment has the following properties: (1) Optical performance: The peak transmittance in the wavelength range of 300 nm to 1100 nm is 91.0% (corresponding wavelength of 621 nm, including glass substrate), and the average transmittance in the wavelength range of 400 nm to 800 nm is 84.9% (including glass substrate). (2) Electrical properties: The thin film resistivity is 0.23 Ω·cm; (3) Hydrophobic properties: The static water contact angle of the surface is 109°; (4) Surface morphology: The root mean square roughness of the surface is 8.25 nm; (5) Mechanical properties: A 9H pencil does not leave visible scratches on the film surface, and the pencil hardness is not less than 9H.
[0045] Example 6 In this embodiment, an AZO target with an alumina to zinc oxide mass ratio of 0.02:1 was selected. The sputtering process conditions were: substrate temperature of 300℃ and AZO target sputtering power density of 1.5 W / cm³. 2 The working atmosphere in the magnetron sputtering cavity is Ar, the gas flow rate is 30 sccm, the working pressure is 3 Pa, and the deposition time is adjusted according to the target thickness. The film thickness in this embodiment is approximately 160 nm.
[0046] The aluminum-doped zinc oxide transparent conductive hydrophobic thin film prepared in this embodiment has the following properties: (1) Optical performance: The peak transmittance in the wavelength range of 300 nm to 1100 nm is 91.9% (corresponding to a wavelength of 621 nm, including the glass substrate), and the average transmittance in the wavelength range of 400 nm to 800 nm is 86.5% (including the glass substrate). (2) Electrical properties: The thin film resistivity is 1.24 × 10⁻⁶. -2 Ω·cm; (3) Hydrophobic properties: The static water contact angle of the surface is 110°; (4) Surface morphology: The root mean square roughness of the surface is 4.29 nm; (5) Mechanical properties: A 9H pencil does not leave visible scratches on the film surface, and the pencil hardness is not less than 9H.
[0047] Example 7 In this embodiment, an AZO target with an alumina to zinc oxide mass ratio of 0.02:1 was selected. The sputtering process conditions were: substrate temperature of 300℃ and AZO target sputtering power density of 1 W / cm³. 2 The working atmosphere in the magnetron sputtering cavity is Ar, the gas flow rate is 30 sccm, the working pressure is 3 Pa, and the deposition time is adjusted according to the target thickness. The film thickness in this embodiment is approximately 170 nm.
[0048] The aluminum-doped zinc oxide transparent conductive hydrophobic thin film prepared in this embodiment has the following properties: (1) Optical performance: The peak transmittance in the wavelength range of 300 nm to 1100 nm is 92.2% (corresponding to a wavelength of 501 nm, including the glass substrate), and the average transmittance in the wavelength range of 400 nm to 800 nm is 84.3% (including the glass substrate). (2) Electrical properties: The thin film resistivity is 1.69 × 10⁻⁶. -2 Ω·cm; (3) Hydrophobic properties: The static water contact angle of the surface is 122°; (4) Surface morphology: The root mean square roughness of the surface is 3.77 nm; (5) Mechanical properties: A 9H pencil does not leave visible scratches on the film surface, and the pencil hardness is not less than 9H.
[0049] Example 8 In this embodiment, an AZO target with an alumina to zinc oxide mass ratio of 0.04:1 was selected. The sputtering process conditions were: substrate temperature of 300℃ and AZO target sputtering power density of 2 W / cm³. 2The working atmosphere in the magnetron sputtering cavity is Ar, the gas flow rate is 30 sccm, the working pressure is 3 Pa, and the deposition time is adjusted according to the target thickness. The film thickness in this embodiment is approximately 170 nm.
[0050] The aluminum-doped zinc oxide transparent conductive hydrophobic thin film prepared in this embodiment has the following properties: (1) Optical performance: The peak transmittance in the wavelength range of 300 nm to 1100 nm is 91.2% (corresponding to a wavelength of 637 nm, including the glass substrate), and the average transmittance in the wavelength range of 400 nm to 800 nm is 86.4% (including the glass substrate). (2) Electrical properties: The thin film resistivity is 8.4 × 10⁻⁶. -3 Ω·cm; (3) Hydrophobic properties: The static water contact angle of the surface is 118°; (4) Surface morphology: The root mean square roughness of the surface is 9.72 nm; (4) Mechanical properties: The pencil hardness shall not be less than 9H.
[0051] Figure 9 The influence of process parameters on the hydrophobic properties (static water contact angle) of the thin film is further presented.
[0052] like Figure 9 As shown in (a), at a fixed sputtering power density of 2 W / cm 2 Under a substrate temperature of 300℃, as the sputtering working pressure increased from 1 Pa to 4 Pa, the static water contact angles on the film surface were 114°, 116°, 116°, and 118°, respectively. Throughout the entire test pressure range, the contact angle remained consistently above 105°. When the pressure rose above 3 Pa, a uniformly distributed nanoscale island-like grain cluster morphology formed on the film surface, with shallow grooves separating the grains. The surface roughness increased significantly, and this surface texture effectively amplified the intrinsic hydrophobicity of the material under the Wenzel effect.
[0053] like Figure 9 As shown in (b), at a fixed sputtering power density of 2 W / cm² 2 Under a working pressure of 3 Pa, as the substrate temperature increased from 25°C to 400°C, the static water contact angles on the film surface were 110°, 109°, 112°, 116°, and 122°, respectively. Within a wide temperature range of 25°C to 400°C, the contact angles were consistently higher than 105°; and with increasing temperature, the contact angles gradually increased, reaching a maximum of 122° at 400°C. This indicates that the present invention achieves excellent hydrophobic properties across a wide temperature window from room temperature to 400°C, making it particularly suitable for temperature-sensitive flexible substrates or low-energy-consumption fabrication requirements.
[0054] Comparative Example 1 To investigate the effect of sputtering power density on the overall performance of the thin film, this comparative example was subjected to comparative experiments under power density conditions exceeding the limits of this invention.
[0055] An AZO target with an alumina to zinc oxide mass ratio of 0.02:1 was selected, and an AZO thin film was deposited on a glass substrate using DC magnetron sputtering. Sputtering conditions: substrate temperature 400℃, AZO target power density 4 W / cm³. 2 (Exceeding the 0.5 W / cm limit specified in this invention) 2 ~2 W / cm 2 (Range), Ar gas flow rate 30 sccm, working pressure 3 Pa.
[0056] The resistivity of the AZO thin film prepared by the above method is 7.2 × 10⁻⁶. -4 Ω·cm; The static water contact angle of the surface, measured using the seated drop method with deionized water as the test droplet, was 82.5° (see [reference]). Figure 10 It does not reach the hydrophobic level (contact angle <90°).
[0057] The comparative results show that at excessively high power densities (4 W / cm²), 2 Under these conditions, although the thin film achieved higher conductivity, its contact angle was only 82.5°, exhibiting hydrophilic properties. Analyzing the physical nature of AZO materials, the reason for this is: high power density significantly increases sputtering yield, resulting in an excessively fast deposition rate, and Al... 3+ The substitution degree in the ZnO lattice is significantly increased, and a large number of oxygen vacancies are formed to maintain charge balance and release lattice stress.
[0058] Oxygen vacancies act as doubly ionized donors, releasing free electrons and increasing the carrier concentration and decreasing the resistivity of the thin film. However, excess oxygen vacancies significantly increase the number of surface coordinating unsaturated active sites, which act as Lewis acid sites to adsorb environmental water molecules and promote their dissociation into surface hydroxyl groups. This leads to a substantial increase in surface polarity and surface free energy, resulting in strong hydrophilic properties in the thin film.
[0059] This comparative example, compared with Examples 1-7, shows that at 0.5 W / cm²... 2 ~2 W / cm 2 Within the power density range, a moderate deposition rate effectively limits the degree of aluminum substitution and the resulting oxygen vacancy proliferation, enabling the film to maintain usable conductivity while reducing the surface free energy to a level sufficient to achieve hydrophobicity.
[0060] Comparative Example 2 To investigate the effect of working pressure on the hydrophobic properties of the thin film, this comparative example was subjected to a comparative experiment under air pressure conditions lower than those specified in this invention.
[0061] An AZO target with an alumina to zinc oxide mass ratio of 0.02:1 was selected, and an AZO thin film was deposited on a glass substrate using DC magnetron sputtering. Sputtering conditions: substrate temperature 400℃, AZO target power density 2 W / cm³. 2 Ar gas flow rate 30 sccm, working pressure 0.8 Pa (lower than the 3 Pa to 4 Pa range specified in this invention).
[0062] The resistivity of the AZO thin film prepared by the above method is 7.0 × 10⁻⁶. -4 Ω·cm; the static water contact angle of the surface measured using the seated drop method with deionized water as the test droplet was 73.5° (see [reference]). Figure 11 ).
[0063] The comparative results show that under excessively low operating pressure (0.8 Pa), the contact angle of the film is only 73.5°, exhibiting obvious hydrophilic properties. The reason for this, analyzed in conjunction with the physical nature of AZO materials, is that the mean free path of sputtered particles increases under low pressure, carrying excessive kinetic energy upon reaching the substrate. This bombards the surface of the grown film, causing lattice atomic displacement and the generation of numerous point defects (especially oxygen vacancies). The increased oxygen vacancy concentration leads to an increase in Lewis acid active sites on the surface, causing water molecules to dissociate and adsorb on the surface, generating hydroxyl groups, thus increasing the surface free energy and resulting in the hydrophilic properties of the film.
[0064] The comparison between this comparative example and Examples 1-7 shows that, within the working pressure range of 3 Pa to 4 Pa, the moderate reduction in particle kinetic energy effectively suppresses lattice damage and oxygen vacancy formation caused by high-energy particle bombardment, ensuring low oxygen vacancy concentration and high-quality crystallization of the film, thus providing a chemical basis for the realization of hydrophobicity.
Claims
1. An aluminum-doped zinc oxide transparent conductive hydrophobic thin film, comprising a transparent substrate and an aluminum-doped zinc oxide thin film layer deposited on the surface of the transparent substrate, characterized in that, The mass ratio of aluminum oxide to zinc oxide in the aluminum-doped zinc oxide transparent conductive hydrophobic thin film layer is 0.02~0.04:1; The resistivity of the aluminum-doped zinc oxide transparent conductive hydrophobic film is 1×10⁻⁶. -3 ~1.5 Ω·cm; The surface static water contact angle of the aluminum-doped zinc oxide transparent conductive hydrophobic film is 105~125°.
2. The aluminum-doped zinc oxide transparent conductive hydrophobic thin film according to claim 1, characterized in that, The preferred crystal orientation of the aluminum-doped zinc oxide thin film layer is the (002) crystal plane.
3. The aluminum-doped zinc oxide transparent conductive hydrophobic thin film according to claim 1, characterized in that, The pencil hardness of the aluminum-doped zinc oxide transparent conductive hydrophobic film is not less than 9H.
4. The aluminum-doped zinc oxide transparent conductive hydrophobic thin film according to claim 1, characterized in that, The surface of the aluminum-doped zinc oxide thin film layer has island-like protrusions, interwoven nanoridges, or interconnected network-like nanoscale surface textures.
5. The aluminum-doped zinc oxide transparent conductive hydrophobic thin film according to claim 4, characterized in that, The root mean square roughness of the aluminum-doped zinc oxide thin film layer is 2~14 nm.
6. The aluminum-doped zinc oxide transparent conductive hydrophobic thin film according to any one of claims 1 to 5, characterized in that, Aluminum-doped zinc oxide thin films were prepared by single-step deposition on a transparent substrate using DC magnetron sputtering. Specific process parameters are as follows: (1) Target material: Aluminum-doped zinc oxide ceramic target material with an alumina to zinc oxide mass ratio of 0.02~0.04:1; (2) Sputtering working gas: Argon gas with a purity of not less than 99.99%, wherein the sputtering working gas is composed of argon gas; (3) Sputtering power density: 0.5~2 W / cm 2 ; (4) Sputtering working pressure: 3~4 Pa; (5) Substrate temperature: 20~400 ℃.
7. The preparation method according to claim 6, characterized in that, The sputtering power density is 1~2 W / cm² 2 .
8. The preparation method according to claim 6, characterized in that, The substrate temperature is 300~400 ℃.
9. The application of the aluminum-doped zinc oxide transparent conductive hydrophobic thin film according to any one of claims 1 to 5 in solar cells, flat panel display panels, touch screens, optical lenses, transparent electric heating devices, anti-fouling coatings for architectural glass, or automotive glass.
Citation Information
Patent Citations
Preparation method for large-area aluminum-doped zinc oxide transparent conductive film with high light transmittance and high conductivity
CN112593194A
Preparation method of ultraviolet shielding hydrophobic transparent film
CN119800311A